The views of female rape survivors regarding the management received at an emergency unit in the North West province - Mosang, Koonyatse Maureen (2015)

(untitled)
Sexual assault is a global public health and human rights challenge which cuts across all social classes. According to a literature review based on 50 studies from around the world, between 10% and 50% of women have experienced some act of physical violence while one in every four women experience sexual violence by an intimate partner at some point in their lives. In an emergency unit in the North West, South Africa there are policies, guidelines and procedures in place with regard to the management of the rape survivors after the incident which focus on a medical orientated approach. The views of female rape survivors on their management are neglected; therefore management is not patient-centred. The main objective of the study was to explore and describe the views of the female rape survivors regarding the management they received in emergency unit to enable the health care professionals to move towards a more patient-centred approach in the management these patients. Appreciative Inquiry was used a research methodology. A qualitative design using purposive sampling was used to select the participants. Unstructured interviews were conducted with 10 female rape survivors and Tesch steps were used to analyse the data. Three main themes were identified, namely 1) therapeutic environment, 2) optimal healthcare received and 3) excellence in service delivery. With regard to the disease orientated management received the female rape survivors found it to be good. The participants voiced that it is important that female rape survivors should have an opportunity to attend group therapy following the rape incident so that they are able to support each other. === Dissertation (MCur)--University of Pretoria, 2014. === lk2014 === Nursing Science === MCur === Unrestricted